Comics in Reading Comprehension Enhancement to Disseminate Nationhood and Patriotism - Ajurun Begum Ahamed; Muhammad Shamshinor Abdul Azzis (Universiti Sains Islam Malaysia, 2024)
Instilling the knowledge and value of nationhood has been conducted most of the time using linear form of writing in the National Language. The National Language is utilized because it is a language to be mastered by all the citizens of Malaysia. However there should be a diversity in the types of materials in dispersing nationhood and patriotism among the young generation. Nationhood and patriotism values should also be imparted through materials such as the comics. Materials regarding nationhood of Malaysia are also present in abundance in English. Hence the second language should also be used to inculcate nationhood and patriotism. It would contribute greater to the knowledge in history of Malaysia. The incapability in comprehending the materials read on nationhood and patriotism would hinder the students from obtaining knowledge and values of nationhood. The study focused on enhancing reading comprehension among the secondary school students in the notion of enabling them to read and understand nationhood reading materials regardless of types of text and language used.